La figura del chiasmo nelle lettere di Hölderlin (Studia theodisca, 2017)
This essay contends that the figure of speech chiasmus plays a central role in Hölderlin’s oeuvre, not only stylistically but also as a form of organizing thoughts. Evidence is given through some examples taken from the poet’s letters. Thus, the presence of recurring elements in Hölderlin’s epistolary style, irrespective of obvious adjustments to circumstances and addressees, can be seen as the starting point for new insights into the poet’s thinking and writing.